2017
DOI: 10.17706/jcp.12.3.212-220
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation System for Criminal Behavioral Analysis on Social Network using Genetic Weighted K-Means Clustering

Abstract: The accessibility and usage of social networking sites constructs both prospects and menaces for the users. In this research article, we propose a new recommendation system for predicting and recommending the criminal behavioral users on social network based upon the activities of the users. Our recommender system uses the proposed nine factor analysis method, clustering technique called Genetic Weighted K-Means clustering (GWKMC) and the existing classification algorithm namely Negative Selection Algorithm (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Prior studies found that the influence of several factors, such as social, demographic, and economic, significantly impacts crime occurrence (Ranson, 2014;Soundarya et al, 2017;Stansfield et al, 2017). It has been observed that multivariate analysis in crime forecasting is beneficial in improving forecasting performance capabilities.…”
Section: Literature Study On Feature Selection In Crime Forecastingmentioning
confidence: 99%
“…Prior studies found that the influence of several factors, such as social, demographic, and economic, significantly impacts crime occurrence (Ranson, 2014;Soundarya et al, 2017;Stansfield et al, 2017). It has been observed that multivariate analysis in crime forecasting is beneficial in improving forecasting performance capabilities.…”
Section: Literature Study On Feature Selection In Crime Forecastingmentioning
confidence: 99%
“…Anjomshoa et al [21] proposed a scheme which is used for identification of social behavior using machine learning. In this scheme an intelligent system makes which enable to identify user continuously on social network.…”
Section: Related Workmentioning
confidence: 99%